Cost-effectiveness of Treatments for Heavy Menstrual Bleeding. Issue 3 (March 2018) - Spencer, Jennifer C.; Louie, Michelle; Moulder, Janelle K.; Ellis, Victoria; Schiff, Lauren D.; Toubia, Tarek; Siedhoff, Matthew T.; Wheeler, Stephanie B.
Abstract : (Abstracted from Am J Obstet Gynecol 2017;217(5):574.e1–574.e9) In the United States, heavy menstrual bleeding accounts for one-third of all gynecology visits. Multiple treatment options exist for women with symptoms that cannot be controlled with more conservative methods such as oral contraceptives.